Non-hemodynamic factors associated to the risk of developing hypertensive cardiopathy - Álvarez-Aliaga, Alexis; González-Aguilera, Julio César; Maceo-Gómez, Liliana del Rosario; Llano Sosa, Lic David del; Leyva-Castro, Raúl; Ojeda-Vázquez, Rosa (Journal of Cardiology and Cardiovascular Medicine, 2017)
Introduction: Hypertensive cardiopathy is the target organ lesion caused by arterial hypertension (HTN) that exhibits the highest morbidity and mortality rates. Although the importance of hemodynamic overload exerted by HTN on the onset of cardiopathy is well established, several non-hemodynamic factors may contribute significantly to its development. Objective: To evaluate the influence of different non-hemodynamic risk factors in the development of hypertensive cardiopathy. Methods: A prospective cohort study was carried out in hypertensive patients assisted at the specialized arterial hypertension physicians’ office of the “Carlos Manuel de Céspedes” Specialty Policlinic attached to the General University Hospital, Bayamo Municipality, Granma Province, Cuba from January 5, 2006 to December 31, 2015. The study included 18-to-55-year-old hypertensive patients with a stage 1 arterial hypertension diagnosis for less than a year1. Results: The multivariate analysis showed a significant and independent relation among the majority of the factors studied and the risk of developing cardiopathy. The major factor was C-reactive protein (HR: 5.020; IC 95%: 3.383-7,448; p<0.005) followed by microalbuminuria (HR: 2.649; IC 95%: 1.932-3.631; p<0.005). The area under the model ROC curve was 0.887 (p<0,005). Conclusions: The results showed that it is possible to estimate the risk of developing hypertensive cardiopathy with the application of the regression model to major risk factors.